Safi, Louay. “The Concept of Freedom in the West: Between Theory and Practice,” Year 8, Issues 31-32 (Winter 1424 AH/ 2003 CE), Pp. 229-244. - صافي, لؤي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2003)
Louay Safi’s article focuses on the concept of freedom as one of the major concepts that govern the human consciousness, attempting to expose the paradox of freedom in modernist Western thought. The article addresses the question of freedom and historical exclusivity, freedom and the liberation of the individual from social constraints, freedom and conformity between the will of the individual and society, freedom being synonymous with rationality, freedom being synonymous with power, freedom in the context of the two extremes (i.e., limitless freedom vs. domination), and the intersection between the discourses of freedom and domination in the practices of the modern state. It concludes with an explanation of the concept of freedom in light of the modernist Western model.